Perlindungan Hukum Terhadap Pembeli Dalam Perjanjian Pengikat Jual Beli Rumah (Studi Kasus di PT. Fajar Bangun Raharja Kota Surakarta) - ASTASARI, ADHISTHITHA PARATMA; , Darsono, S.H., M.Hum (2017)
Ensuring legal certainty for the buyer as well as the role developer or developer who feels quite credible in drafting agreements binding sale and purchase shall by guided by the provisions of the laws in force in order that legal safeguards contained there in may apply and truly based on the collective agreement and it is expected that the agreement binding sale and purchase can go smoothly and do not cause problems in the future, especially for the home buyer. The lack of clarity and the inclusion of a clause on the exoneration and material agreements lopsided that are aggravating the purchaser in the agreements binding sale and purchase should be anticipated as well as the buyer as a layman who was consumer behavior not only given the freedom to read and learn about the contents of the agreement and should be given the understanding and interpretation so that buyer do not get stuck in content of the agreement from the outside even though it contains a different meaning in clause binding sale and purchase agreement.